Contract farming, profitability, and adoption of food safety measures in broiler production in Bangladesh - Roy, Devesh; Tripathi, Gaurav; Islam, Abu Hayat Md. Saiful; Kumar, Anjani (International Food Policy Research Institute, 2021)
This study, based on a primary survey conducted in Bangladesh in 2016, assesses the impact of contract farming in broiler production on profits and the adoption of food safety measures at the farm level. It also estimates the determinants for participation in contract farming, finding a farmer’s education and broiler-housing structure to be significant determinants. This study uniquely assesses the association of contract farming with the provision of well-defined food safety attributes. It finds that contract participation enhances farmers’ net returns by as much as 215–280% and raises compliance with food safety measures by around 13%. Increased productivity and provision of non-price attributes such as food safety in the product account for the difference in farmer returns.